/phǔa/ /mia/ : THE DIVERSITY OF MEANING - Iamsa-ard , Bhasrvarin; Kingkham, Wilaisak (Journal of Educational Review Faculty of Education in MCU, 2021)
The article aimed to present the diversity of meaning of /phǔa/ /mia/ and the synonyms: /sǎ:mi:/, /sâwǎ:mi:/, /phâríja:/ and /phanrája:/ in the spouse law and diachronic documents. Likewise, this article also indicated the meaning in current Thai that related to the dynamic of language. /phǔa/ /mia/ in the past signified that man or woman who were a spouse in legality and behavior. Since the spouse law Amendment Act, B.E. 2473 (1930) came into force, this Amendment Act enacted /phǔa/ /mia/ or /sǎ:mi:/ /phâríja:/, the forms in this Amendment Act, had to register a marriage certificate. Therefore, it was a definition in another way. However, these words were highly changed in current Thai. These words can be used in various contexts that differed from the spouse law and Royal Institute Dictionary. This phenomenon caused by speakers in each register and concept about the prestige of language.